PERAN PENDIDIKAN AGAMA KRISTEN DALAM MEMBENTUK KARAKTER DAN NILAI MORAL PESERTA DIDIK DI TENGAH TANTANGAN PERKEMBANGAN ZAMAN - Sinta Meriana Suli; Monika Paruku; Yolanda Tiku La'bi; Ritayani; Dayus Melson Sumanda (CV. ADIBA AISHA AMIRA, 2026)
Christian Religious Education plays a crucial role in shaping the character and moral values of students amidst increasingly complex developments. Technological advancements, globalization, and social change bring with them various influences that can impact the mindset, attitudes, and behavior of the younger generation. Therefore, education should not only focus on academic achievement but also on character formation based on moral and spiritual values. This study aims to examine the role of Christian Religious Education in shaping the character and moral values ​​of students and to identify the challenges faced in its implementation. The research method used is a qualitative approach with a library research type through a review of various relevant scientific literature. The results show that Christian Religious Education plays a crucial role in instilling the values ​​of love, honesty, responsibility, and social concern through the learning process, teacher role models, and ongoing character development. Strengthening Christian Religious Education also requires collaboration between schools, families, and churches so that the process of character formation of students can take place effectively and sustainably.